2007
DOI: 10.1093/jxb/erm127
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance signalling of abscisic acid (ABA): the factors regulating the intensity of the ABA signal

Abstract: Abscisic acid (ABA) is a stress signal, which moves in the xylem from the roots to the aerial parts of the plant, where it regulates stomatal movement and the activity of shoot meristems. Root growth-promoting microorganisms in the rhizosphere, lateral ABA flows in the root cortex across apoplastic barriers, ABA redistribution in the stem, leaf apoplastic pH values, and the action of beta-glucosidases, both in the apoplast and the cytosol of the mesophyll, play an important role in the regulation of signal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
185
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(198 citation statements)
references
References 26 publications
9
185
0
4
Order By: Relevance
“…Relatively high levels of ABA were detected in the spent media, as compared with most of the tested CK derivatives, with the only exception being methylthiols. The observed specific ABA distribution between Euglena cells and the slightly alkaline growth medium (pH 7.5) is in accordance with the previous report, that ABA transport in vascular plants is regulated by apoplastic pH of the leaf and stem and its flow in the plant intensifies with the increasing pH of the tissue (Jiang & Hartung, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Relatively high levels of ABA were detected in the spent media, as compared with most of the tested CK derivatives, with the only exception being methylthiols. The observed specific ABA distribution between Euglena cells and the slightly alkaline growth medium (pH 7.5) is in accordance with the previous report, that ABA transport in vascular plants is regulated by apoplastic pH of the leaf and stem and its flow in the plant intensifies with the increasing pH of the tissue (Jiang & Hartung, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Abscisic acid (ABA) is a phytohormone that plays an important role in plant responses to environmental stress and plant pathogens (Jiang & Hartung, 2008;Santner et al, 2009). The general functions of ABA in vascular plants are to inhibit precocious germination and promote dormancy in seeds, and production of molecules that protect cells against desiccation (Nakashima & Yamaguchi-Shinozaki, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In response, patterns of root growth are altered, with some root tips inhibited and others stimulated, and stomata in the leaf close (Daszkowska-Golec and Szarejko, 2013;Harris, 2015). The rapid increase in xylem sap ABA in response to salinity is thought to be due to multiple sources: increased biosynthesis, phloem import of ABA from the leaves to the roots, and release of ABA from the conjugated form, ABAglucose ester (ABA-GE) (Jiang and Hartung, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike jasmonic acid, which is most active when conjugated to isoleucine (Staswick and Tiryaki, 2004), ABA conjugates are thought to be inactive forms, which are stored in the vacuole and transported in the xylem (Jiang and Hartung, 2008). In response to salt stress, ABA can be rapidly released from ABA-GE by b-glucosidases in the endoplasm reticulum (ER) or the cell wall space (Dietz et al, 2000;Lee et al, 2006) In Arabidopsis, b-GLUCOSIDASE1 (BG1) has been shown to function in the ER to release ABA from ABA-GE stores in response to salt stress (Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Long-distance transport of ABA from roots to leaves has been extensively discussed in relation to stomatal closure in response to water deficit (7)(8)(9)(10)(11). Stomata closed when a part of the root system was exposed to water stress, whereas the leaf water status was unchanged (11).…”
mentioning
confidence: 99%